Evaluating the Aquatic Habitat Potential of Flooded Polders in the Sacramento-San Joaquin Delta - John R. Durand (San Francisco Estuary and Watershed Science, 2017)
https://doi.org/10.15447/sfews.2017v15iss4art4 Large tracts of land in the Sacramento-San Joaquin Delta are subsided due to agricultural practices, creating polders up to 10 m below sea level that are vulnerable to flooding. As protective dikes breach, these become shallow, open water habitats that will not resemble any historical state. I investigated physical and biotic drivers of novel flooded polder habitat, using a Native Species Benefit Index (NSBI) to predict the nature of future Delta ecosystems. Results suggest that flooded polders in the north Delta will have the ecology and fish community composition of a tidal river plain, those in the Cache-Lindsey Complex will have that of a tidal backwater, those in the confluence of the Sacramento and San Joaquin Rivers a brackish estuary, and those in the south Delta a fresh water lake. Flooded east-side Delta polders will likely be a transitional zone between south Delta lake-like ecosystems and north Delta tidal river plains. I compared each regional zone with the limited available literature and data on local fish assemblies to find support for NSBI predictions. Because flood probabilities and repair prioritization analyses suggest that polders in the south Delta are most likely to flood and be abandoned, without extensive intervention, much of the Delta will become a freshwater lake ecosystem, dominated by alien species. Proactive management of flooded tracts will nearly always hedge risks, save money and offer more functional habitats in the future; however, without proper immediate incentives, it will be difficult to encourage strong management practices.